2021
DOI: 10.1108/aia-09-2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

Teaching a child with autism to request help only when needed

Abstract: Purpose Children with autism spectrum disorders (ASD) or other developmental disabilities are often reported to have challenges in well generalizing the newly learned communicative skills such as requesting help. Not requesting help when it is needed can hinder engagement and learning, whereas requesting help could also be socially inappropriate. This paper aims to offer a demonstration of applying general case instruction to teach a young child diagnosed with ASD to request help only when needed while concurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Saying "goldfish, please" is a discriminated positively reinforced explicit mand if the child asks for goldfish after they have not had access to a snack for several hours (i.e., state of deprivation present) and refrain from asking for goldfish after they just ate a bag of goldfish (i.e., state of deprivation absent). Although several researchers have demonstrated the effectiveness of mand training in teaching discriminated positively reinforced mands to children with ASD (e.g., Carnett et al, 2019;Chezan, Drasgow, Legg, & Hollborn, 2016;Chezan et al, 2019;Gutierrez et al, 2007Gutierrez et al, , 2010, the literature on discriminated positively reinforced explicit mands is relatively limited and needs further investigation (Chen, 2019;Chen et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Saying "goldfish, please" is a discriminated positively reinforced explicit mand if the child asks for goldfish after they have not had access to a snack for several hours (i.e., state of deprivation present) and refrain from asking for goldfish after they just ate a bag of goldfish (i.e., state of deprivation absent). Although several researchers have demonstrated the effectiveness of mand training in teaching discriminated positively reinforced mands to children with ASD (e.g., Carnett et al, 2019;Chezan, Drasgow, Legg, & Hollborn, 2016;Chezan et al, 2019;Gutierrez et al, 2007Gutierrez et al, , 2010, the literature on discriminated positively reinforced explicit mands is relatively limited and needs further investigation (Chen, 2019;Chen et al, 2021).…”
mentioning
confidence: 99%
“…Enhancing the mand repertoire of children with ASD has been associated with the development of their overall verbal behavior. For example, researchers have demonstrated that teaching children with ASD to mand for preferred items or activities increased their spontaneous verbal behavior (Charlop et al, 1985; Sweeney-Kerwin et al, 2007), fostered the acquisition of other verbal operants such as tacts (DeSouza et al, 2017), resulted in improved interpersonal communication and community functioning (Chen et al, 2022), and produced a decrease in problem behavior (e.g., Choi et al, 2010; Chow et al, 2018; Falcomata et al, 2013; Fritz et al, 2013; Kreibich et al, 2015). The findings of these studies revealed the critical importance of mands to children’s verbal behavior and their effective functioning in the natural environment and, thus, highlighted the need to implement effective language intervention programs.…”
mentioning
confidence: 99%